Institutionalising Islamic Pedagogical Ethos through Professional Learning Communities: A Case Study at SDIT Ibadurrahman Srengat Blitar - Sifa’ul Af’idah; Bagus Jamroji (Immortalis Journal of Interdisciplinary Studies, 2026)
This study analyses how teachers’ Islamic pedagogical ethos is institutionalised and how it contributes to the development of students’ adab in an Islamic primary school. It addresses the persistent gap between the normative ideals of Islamic education and their practical implementation. Unlike prior studies that view pedagogical ethos as an individual attribute, this research conceptualises it as a collective, institutional construct embedded within school culture. A qualitative case study was conducted at SDIT Ibadurrahman Srengat, Blitar. Data were collected through in-depth semi-structured interviews with the principal, teachers, and students. The data were analysed using interpretative thematic analysis, with triangulation employed to enhance credibility and validity. The study reveals a structured, multi-layered model of Islamic pedagogical ethos aligned with the Professional Learning Community (PLC) framework. This model operates across institutional, pedagogical, and daily praxis levels, showing that Islamic pedagogical ethos is systematically developed through cycles of value internalisation, collaborative engagement, and reflective practice. The process fosters sustained cultivation of students’ adab within the school environment. By integrating PLC principles with Islamic value internalisation, this study provides a novel, operational, and sustainable framework for character education in Islamic schooling. The findings offer practical guidance for educational leaders and teachers seeking to institutionalise Islamic pedagogical values and support the holistic development of students.